How to Tell a Program from an Automobile - Lamport, Leslie (In A Dynamic and Quick Intellect, John Tromp editor (1996)–a Liber Amicorum issued by the CWI in honor of Paul Vitanyi's 25-year jubilee., 1977)
I wrote this brief note in January, 1977. It came about because I was struck by the use of the term program maintenance, which conjured up in my mind images of lubricating the branch statements and cleaning the pointers. So, I wrote this to make the observation that programs are mathematical objects that can be analyzed logically. I was unprepared for the strong emotions this stirred up among my colleagues at Massachusetts Computer Associates, who objected vehemently to my thesis. So, I let the whole thing drop. Years later, when I was invited to submit a short paper for the volume honoring Vitanyi, I decided that this paper would be appropriate because he had learned to drive only a few years earlier. The paper retains its relevance, since programmers still don't seem to understand the difference between a program and an automobile.